IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL DI RSUD UNDATA PROVINSI SULAWESI TENGAH - Ridwan, Bahria (Katalogis, 2017)
This research aimed at improving and explaining the phenomenon of policy implementation of Minimum Service Standar in Regional Hospital of Undata. Research method used is a qualitative method with data colection technique conducted through observation, interviews and documentation. Informants of this research aredetermined purposively on Undata Hospital employees who are deemed to understand and know about aspects of this research. Data were analysed using the Interactive Model by Milles and Huberman namely data collection, data reduction and display and conclusion/verification. The main guided as theory analytic is a model of policy implementation developed by Edward III which consists of aspects of Communication, Resources, Implementersâ€™ Attitude/Dispotition and Bureaucratic Structure. The research result shows that the implementation of minimum service standar policy public on Undata Hospital of Central Sulawesi Province is generally in good enough categories. Of the four aspects investigated, aspect ofÂ the communication aspect that has not gone well because the executor has not done it in a clear and consistent so the impact on policy objectives have not been able to understand the intent and policy objectives. Then aspect of the resources of amount employee reource, competency and skill of employee and facilities is effective enough. On dispotition aspect which consist of supporting, attitude and manner, has been shown good improvent. In bureaucracy structure with theÂ aspect of standard operational procedure, has been followed propoerly, but it only needs to increase the consistency with more strict rules.